Qualitative longitudinal research: Application, potentials and challenges in the context of migration research - Aleksandra Winiarska (University of Warsaw, Centre of Migration Research (CMR), 2017)
The aim of this working paper is to review the possible applications, potentials and methodological challenges of qualitative longitudinal research (QLR) in the context of migration studies. It is based on a literature review of both theoretical and empirical papers focused on QLR as such, or discussing various specific elements related to this approach. I start by giving a brief overview of the characteristic features and potentials of QLR as acknowledged by different authors. Next I move on to unwrap the numerous methodological and practical aspects important to QLR, including building and retaining an adequate research sample (especially in the case of mobile and spatially dispersed populations) as well as reflexions on research methodology (including also online interviewing). I then turn to the stage of data analysis and finally acknowledge ethical issues, especially concerning anonymity and researcher-participant relationships. Throughout the text I reflect on the possible applications of this approach to migration studies, including also multiple migration.
Keywords: 330; Qualitative Longitudinal Research; Migration